Consumer Behavior Research of Electronic Money Business in Indonesia and A Marketing Proposal (Subject: Flazz BCA) - Diggy Afrizal, Muchammad; Sufiati Purwanegara, Mustika (The Indonesian Journal of Business Administration, 2016)
Abstract - The development of information technology have an impact in various fields, including payment systems, particularly with the advent of electronic retail payment system known as electronic money (e-money). In the future, industries with electronic system predicted will be growing significantly. But compare with the other non-cash payment, the e-money in low number. For e-money companies’ issue, the market share of Flazz BCA decline during 2010-2014. The primary objective of this research is to know the behavior of consumer towards the purchase of e-money product Subject Flazz BCA and analysis the business issue. This research also aims to create effective marketing strategy for e-money issuer so it can attract potential consumer and increase the market share. This research using conducted depth interview, questionnaire and SPSS to analyze the data. Sample of 300 respondents were taken to test the hypotheses, and analyzed using multiple regression. The methods of this research is to get deeper analysis about root problem, it uses analysis from internal and external analysis. In which, internal analysis consist of seven P marketing mix and for external consist of general environment, industry analysis and consumer analysis. The research generate some strategies in which to increasing the market share of Flazz BCA and retain the Flazz BCA as a market leader of electronic money business in Indonesia,  it is using SWOT Matrix strategies and Push-Pull strategies, push means that ‘taking the product come to the customer’ and pull means that ‘getting customer taking to you’. This research is expected to be able to give a mapping explanation about consumer behavior and marketing strategies in Indonesia and able to provide sufficient information for companies who might have product to serve this segment also for further observation. Keywords: electronic money, consumer behavior, marketing strategies, willingness to use, Flazz BCA